De‐Escalated Adjuvant Therapy After Transoral Robotic Surgery for Human Papillomavirus‐Related Oropharyngeal Carcinoma: The Sinai Robotic Surgery (SIRS) Trial - Miles, Brett A.; Posner, Marshall R.; Gupta, Vishal; Teng, Marita S.; Bakst, Richard L.; Yao, Mike; Misiukiewicz, Kryzsztof J.; Chai, Raymond L.; Sharma, Sonam; Westra, William H.; Kim‐Schulze, Seunghee; Dayal, Bheesham; et al. (The oncologist (Dayton, Ohio), 2021)
Background Treatment of human papillomavirus‐related oropharyngeal squamous cell carcinoma (HPVOPC) results in unprecedented high survival rates but possibly unnecessary toxicity. We hypothesized that upfront surgery and neck dissection followed by reduced‐dose adjuvant therapy for early and intermediate HPVOPC would ultimately result in equivalent progression‐free survival (PFS) and overall survival while reducing toxicity. Methods This study was a nonrandomized phase II trial for early‐stage HPVOPC treated with transoral robotic surgery (TORS) followed by reduced‐dose radiotherapy. Patients with previously untreated p16‐positive HPVOPC and <20 pack years’ smoking history were enrolled. After robotic surgery, patients were assigned to group 1 (no poor risk features; surveillance), group 2 (intermediate pathologic risk factors [perineural invasion, lymphovascular invasion]; 50‐Gy radiotherapy), or group 3 (poor prognostic pathologic factors [extranodal extension [ENE], more than three positive lymph nodes and positive margin]; concurrent 56‐Gy chemoradiotherapy with weekly cisplatin). Results Fifty‐four patients were evaluable; there were 25 in group 1, 15 in group 2, and 14 in group 3. Median follow‐up was 43.9 months (9.6–75.8). Disease‐specific survival was 98.1%, and PFS was 90.7%. PFS probability via Kaplan‐Meier was 91.3% for group 1, 86.7% for group 2, and 93.3% for group 3. There were five locoregional failures (LRFs), including one distant metastasis and one contralateral second primary. Average time to LRF was 18.9 months (9.6–59.0); four LRFs were successfully salvaged, and the patients remain disease free (11.0–42.7 months); one subject remains alive with disease. Conclusion The results indicate that upfront surgery with neck dissection with reduced‐dose radiation for T1–2, N1 stage (by the eighth edition American Joint Committee on Cancer staging manual) HPVOPC results in favorable survival with excellent function in this population. These results support radiation dose reduction after TORS as a de‐escalation strategy in HPVOPC. Implications for Practice Transoral robotic surgery can provide a safe platform for de‐escalation in carefully selected patients with early‐stage human papillomavirus‐related oropharyngeal cancer. In this clinical trial, disease‐specific survival was 100%, over 90% of the cohort had a reduction of therapy from standard of care with excellent functional results, and the five patients with observed locoregional failures were successfully salvaged. Treatment of human papillomavirus‐related oropharyngeal squamous cell carcinoma results in high survival rates but unnecessary toxicity. The SIRS trial investigated the use of transoral robotic surgery with selective neck dissection, followed by reduced‐dose adjuvant therapy, to reduce toxicity and maintain overall and progression‐free survival rates.